Multicystic Dysplastic Kidney: Prenatal Compensatory Renal Growth Pattern. (22nd December 2020) - Gilad, Noa; Weissmann‐Brenner, Alina; Gilboa, Yinon; Dekel, Benjamin; Achiron, Reuven; Perlman, Sharon
Abstract : Objectives: To assess the prenatal growth pattern of the normal kidney contralateral to a multicystic dysplastic kidney (MCDK). Methods: A retrospective study was conducted in a single referral center over 4 years. Cases diagnosed prenatally as MCDK and confirmed postnatally constituted the study group. For creation of nomograms, only isolated cases of MCDK were included. Results: Sixty‐one fetuses had a diagnosis of an MCDK during the study period. After exclusion of cases with associated malformations, 47 fetuses remained, providing 94 measurements for creation of nomograms. The growth pattern of the normal kidney contralateral to an MCDK was linear throughout gestation (percentile = 20.01 + 1.5 gestational age; linear R 2 = 0.753; r = 0.868) and was significantly higher during the third trimester (29–38 weeks' gestation) compared to the second trimester (22–28 weeks' gestation; P < .001). A comparison of the growth pattern of the normal kidney contralateral to the MCDK to the growth pattern of a solitary kidney revealed a significant higher compensatory trend during the third trimester ( P < .0001). The mean kidney lengths at 22 and 38 weeks' gestation correlated with the 52nd and 88th and with the 84th and 90th percentiles for the normal kidney contralateral to the MCDK and a solitary kidney, respectively. Conclusions: According to our study, the normal kidney contralateral to an MCDK has a unique growth pattern during intrauterine life, with dominant growth during the third trimester. The exact mechanism for this pattern, in comparison to early renal hypertrophy shown in solitary kidneys, is currently not clear. These data provide relevant information for the multidisciplinary prenatal counseling of future parents regarding the future renal outcome.